Competition Between Red Blood Cell Aggregation and Breakup: Depletion Force due to Filamentous Viruses vs. Shear Flow - Korculanin, O.; Kochetkova, T.; Lettinga, M. P. (Frontiers in Physics, 2021)
Human blood is a shear-thinning fluid with a complex response that strongly depends on the red blood cell's (RBC's) ability to form aggregates, called rouleaux. Despite numerous investigations, microscopic understanding of the break up of RBC aggregates has not been fully elucidated. Here, we present a study of breaking up aggregates consisting of two RBCs (a doublet) during shear flow. We introduce the filamentous fd bacteriophage as a rod-like depletant agent with a very long-range interaction force, tuning the depletion interaction with the rod's concentrations. We visualize the structures while shearing by combining a home-build counter-rotating cone-plate shear cell with microscopy imaging. A diagram of dynamic states for shear rates versus depletant concentration shows regions of different flow responses and separation stages for the RBCs doublets. With increasing interaction forces, the full-contact flow states dominate, such as rolling and tumbling. It is seen that the RBC doublets only undergo separation during tumbling motion when the angle between the normal of the doublets with the flow direction is within a critical range. However, at sufficiently high shear rates, the time spent in the critical range becomes too short, such that the cells continue to tumble without separating.